Prison notebooks - Gramsci, Antonio, 1891-1937; Buttigieg, Joseph A.; Columbia University. Press (New York : Columbia University Press, 1992)
This second volume of Antonio Gramsci's Letters from Prison covers the years 1931 to 1937. Beginning with a letter to Tania Schucht, his sister-in-law, that expresses troubled concern about his wife's family, and ending with a series of notes to his two sons, Delio and Giuliano, these letters chronicle Gramsci's rapidly declining health, his numerous efforts, assisted by Tania and Piero Sraffa, his friend and mentor, to obtain relief from the physical and administrative oppression of imprisonment at Turi, and his transfers from Turi to Civitavecchia, to Formia, and finally to Rome, where he died on April 27, 1937." "What gives the letters in Volume Two their distinctive character is the lucidity with which Gramsci confronts a variety of difficult problems of modern civilization. His exchange of letters with Tania on anti-Semitism are remarkable for their range of historical, political, and psychological considerations. His letters to his ailing wife, Giulia, on Freudianism and psychoanalysis, although brief and fragmentary, reveal fruitful perspectives on the relationship between the individual and society in periods of social and political turmoil. Gramsci's exchange of ideas with Piero Sraffa, mediated by Tania, on the philosophy of Benedetto Croce are indispensable supplements to his ideas on philosophical idealism expressed in the Prison Notebooks." "Also of great interest are the letters in which Gramsci confronts his feelings of estrangement from his wife and children. These emotions prompted him to probe his own psyche with exceptional candor. Gramsci's letters to Giulia are an especially poignant aspect of his attempt to transcend the real and metaphorical walls that prevented full communication with his loved ones. Another series of letters discusses his philosophy of education, as applied to his nieces and nephews in Sardinia, as well as his two sons in Moscow." "Volume Two of Letters from Prison contains explanatory notes, a chronology of Gramsci's life, a bibliography, and an analytical index for the entire two-volume collection.
-- Contents: Vol.1.1991; Vol.2.1996.
Translation of: Quaderni del carcere.
Vol. 2: Edited and translated by Joseph A. Buttigieg.
Includes bibliographical references and indexes.
Keywords: Gramsci, Antonio, -- 1891-1937 -- Notebooks, sketchbooks, etc